2001
DOI: 10.1001/archpsyc.58.4.322
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Effects of Smoked Marijuana by the CB1-Selective Cannabinoid Receptor Antagonist SR141716

Abstract: SR141716 blocked acute psychological and physiological effects of smoked marijuana without altering THC pharmacokinetics. These findings confirm, for the first time in humans, the central role of CB1 receptors in mediating the effects of marijuana.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
252
1
5

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 436 publications
(267 citation statements)
references
References 40 publications
7
252
1
5
Order By: Relevance
“…Most behavioral, cognitive, and psychotropic effects of cannabis result from the effects of Δ9-THC at brain CB 1 Rs. The subjective "high" produced by cannabis can be blocked by pretreatment with the CB 1 R antagonist rimonabant [74]. Δ9-THC impairs short-term working memory in several rodent models, which can be reversed by preapplication of a CB 1 R antagonist [75][76][77][78].…”
Section: δ9-thcmentioning
confidence: 99%
“…Most behavioral, cognitive, and psychotropic effects of cannabis result from the effects of Δ9-THC at brain CB 1 Rs. The subjective "high" produced by cannabis can be blocked by pretreatment with the CB 1 R antagonist rimonabant [74]. Δ9-THC impairs short-term working memory in several rodent models, which can be reversed by preapplication of a CB 1 R antagonist [75][76][77][78].…”
Section: δ9-thcmentioning
confidence: 99%
“…In a study investigating the ability of the CB1 receptor antagonist, rimonabant, to reverse the effects of D 9 THC, Marilyn Heustis and her colleagues found that even very high doses of rimonabant (90 mg) were only modestly effective in reducing most of the subjective components of the 'high' elicited by smoking of a cannabis cigarette. 18 Interestingly, the autonomic effect (tachycardia) elicited by cannabis was more effectively antagonized by rimonabant than the subjective effects, 18 suggesting that the former might be mediated by fatty acid amides and the latter mediated by 2-AG.…”
Section: Interaction Of Endogenous and Exogenous Cannabinoidsmentioning
confidence: 99%
“…The CB1 receptor mediates the positive subjective and reinforcing effects of cannabis (Cooper and Haney, 2008), and the subjective effects of cannabis are attenuated by the CB1 receptor antagonist, rimonabant (Huestis et al, 2001(Huestis et al, , 2007. Further study of rimonabant has, however, been discontinued following evidence that its chronic administration produced side effects such as depression and anxiety (Taylor, 2009), and the manufacturers of other CB1 receptor antagonists approved for testing in humans withdrew their clinical development after rimonabant use was suspended.…”
Section: Introductionmentioning
confidence: 99%